Sustainable Structures and Buildings - Bahrami, Alireza (Springer International Publishing : Imprint: Springer, 2024)
This open access book includes detail on various structures, buildings, and building materials from different structural and sustainability perspectives. It describes how the building and construction industry is vital for the achievement of the sustainable development goals. The aim of this collection is to foster the design and construction of sustainable structures, buildings, and building materials to reduce their environmental impact and connect with the environment. Presenting the knowledge, trends, and developments from a group of contributors in the field working with different kinds of structures, structural components, buildings, and building materials, the book is ideal for practitioners working in commercial settings, as well as engineering students and researchers concerned with sustainability issues. Explains sustainability in the context of structures, buildings, and building materials Demonstrates performance of structures, buildings, and building materials Illustrates trends towards Sustainable Development Goals This book is open access, which means that you have free and unlimited access.